Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep37536
|View full text |Cite
|
Sign up to set email alerts
|

The genome, transcriptome, and proteome of the nematode Steinernema carpocapsae: evolutionary signatures of a pathogenic lifestyle

Abstract: The entomopathogenic nematode Steinernema carpocapsae has been widely used for the biological control of insect pests. It shares a symbiotic relationship with the bacterium Xenorhabdus nematophila, and is emerging as a genetic model to study symbiosis and pathogenesis. We obtained a high-quality draft of the nematode’s genome comprising 84,613,633 bp in 347 scaffolds, with an N50 of 1.24 Mb. To improve annotation, we sequenced both short and long RNA and conducted shotgun proteomic analyses. S. carpocapsae sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 88 publications
1
34
0
Order By: Relevance
“…SOAP2 (version 2.2.1) 2 was used to filter out potential rRNA reads, and the data were filtered to be clean reads. The filtered clean reads were mapped to the reference genome, S. carpocapsae , using HISAT2 (Hierarchical Indexing for Spliced Alignment of Transcripts) 3 ( Rougon-Cardoso et al, 2016 ). The assembled de novo transcriptome was implemented using Trinity ( Grabherr et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOAP2 (version 2.2.1) 2 was used to filter out potential rRNA reads, and the data were filtered to be clean reads. The filtered clean reads were mapped to the reference genome, S. carpocapsae , using HISAT2 (Hierarchical Indexing for Spliced Alignment of Transcripts) 3 ( Rougon-Cardoso et al, 2016 ). The assembled de novo transcriptome was implemented using Trinity ( Grabherr et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptomes and genomes of Steinernema spp. have been characterized (Dillman et al, 2015;Rougon-Cardoso et al, 2016;Yaari et al, 2016;Serra et al, 2019). However, no studies have focused on the specific genes and pathways involved in the heat shock reactions of S. carpocapsae.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, nematodes in the Infective Juvenile (IJ) stage were induced with host insect ( Galleria mellonella ) tissues to detect differentially expressed proteins [12]. In that study, we conducted a qualitative analysis with which we identified 1,154 differentially expressed proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The draft genome assembly of S. carpocapsae ALL strain had 1,578 contigs with an estimated genome size of 85.6 Mb, N50 of 300 kb and more than 28,000 predicted genes (Dillman et al , 2015). Another study, also using short-reads assembled S. carpocapsae Breton strain into 347 scaffolds with an N50 of 1.24 Mb (Rougon-Cardoso et al , 2016). The draft genome status, although helpful, can hinder further studies of protein families’ expansions involved in parasitism.…”
mentioning
confidence: 99%